"Call Me Johanna:" The Challenge of Building Intimacy Between Two Complex Trauma Survivors Within An Analytic Dyad. Issue 1 (2nd January 2016) - Tiemann, Johanna
Abstract : The author describes how her experience as a survivor of developmental trauma informs her work with a patient who is also a survivor of developmental trauma, citing both the assets and liabilities that this history brings to her work as an analyst. An extensive clinical interchange between the author and her patient, June, illustrates how the author's traumatic history both impedes and enhances her work with this patient, focusing on the challenges that creating intimacy between two survivors of trauma presents.